High‐Resolution Evidence for Middle Holocene East Asian Winter and Summer Monsoon Variations: Snapshots of Fossil Coral Records. Issue 16 (21st August 2020) - Asami, Ryuji; Yoshimura, Natsumi; Toriyabe, Hiroto; Minei, Shogo; Shinjo, Ryuichi; Hongo, Chuki; Sakamaki, Takashi; Fujita, Kazuhiko
Abstract: We first generated 53‐, 4‐, 10‐, and 9‐year‐long bimonthly time series of oxygen isotopes (δ 18 O), Sr/Ca, and U/Ca from 4.4 and 4.9 ka corals in Okinawa, Japan. Results indicate that the mid‐Holocene sea surface temperature (SST) and seawater δ 18 O were <1°C lower and 0.1–0.2‰ higher than today. Spectral analyses of reconstructed SST and seawater δ 18 O time series revealed East Asia monsoon (EAM) and El Niño/Southern Oscillation (ENSO) variations. Moreover, the latter had a dominant component of decade‐scale hydrologic variations. The Sr/Ca and U/Ca variations with removal of the ENSO component showed larger fluctuations by 2°C in winter and 0.6°C in summer at 4.4 ka relative to today, demonstrating (slightly) greater influences of the EAM variation on the northwestern subtropical Pacific in winter (summer) at that time, which are probably caused by enhancement of the EAM intensity and/or a southward migration of the latitudinal circulation. Plain Language Summary: Although sediments and stalagmites play a leading role in Quaternary paleoclimate studies, the slow rates of sedimentation frequently preclude from climate reconstruction on a seasonal or interannual timescale. From geochemical records of fossil corals in Okinawa, Japan, we first reconstructed a >50‐year‐long bimonthly time series of sea surface temperature and seawater oxygen isotope ratios (relating to salinity) during the middle Holocene. The high‐resolution climate proxy records clearly showed seasonal‐, interannual‐, and decade‐scale thermal and hydrologic variations. Our data demonstrate that the mean climate state around Okinawa was slightly cooler and saline during the middle Holocene than it is today. It is particularly interesting that we can provide robust evidence for (slightly) greater influence of the East Asian winter (summer) monsoon variability on the northwestern subtropical Pacific sea surface at that time. Our findings can be a key to elucidating latitudinal variations in the intensity and region of middle Holocene East Asian monsoon, possibly associated with El Niño events. Key Points: Mid‐Holocene bimonthly time series of coral climate proxy were generated, exhibiting seasonal, interannual, and decadal timescale variation Coral data demonstrate the East Asia winter monsoon greatly influenced northwestern subtropical Pacific sea surface temperatures at 4.4 ka Reconstructed seawater isotope ratios suggest 10–20 year/cycle hydrological variation dominated the sea surface around the Ryukyu Islands